2004
DOI: 10.1038/sj.ejcn.1602037
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in osteocalcin γ-carboxylation, plasma phylloquinone (vitamin K1) and apolipoprotein E genotype

Abstract: Objective: To investigate plasma osteocalcin g-carboxylation and its relationship to plasma phylloquinone concentration and apolipoprotein E (apoE) genotype in women from three ethnic groups with differing osteoporotic fracture risk. Design and subjects: Fasted blood samples were collected from postmenopausal Gambian (n ¼ 50), British (n ¼ 31) and Chinese women (n ¼ 23), and 11 premenopausal women in each group from three cross-sectional studies. Results: After adjustment for total osteocalcin, plasma undercar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 46 publications
(66 reference statements)
3
17
2
Order By: Relevance
“…In our study, the only significant independent association we found was between the apoE4 allele and higher PIVKA-II concentrations. At present, the direction and magnitude of the effect of apoE genotype on ␥-carboxylation status of peripheral VKDPs remain controversial (11,12). However, this study and our earlier study suggest that the apoE4 allele may be associated with poorer ␥-carboxylation of VKDPs in individuals with CKD.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…In our study, the only significant independent association we found was between the apoE4 allele and higher PIVKA-II concentrations. At present, the direction and magnitude of the effect of apoE genotype on ␥-carboxylation status of peripheral VKDPs remain controversial (11,12). However, this study and our earlier study suggest that the apoE4 allele may be associated with poorer ␥-carboxylation of VKDPs in individuals with CKD.…”
Section: Discussioncontrasting
confidence: 40%
“…Vitamin K status may also be determined by variations in the genes involved in the transport or uptake of vitamin K into liver and bone (apolipoprotein E (apoE)) or those involved in the tissue-specific recycling of vitamin K (Vitamin K Epoxide Reductase (VKOR)). There are few studies evaluating the effect of variations within these two genes and vitamin K status in either the general population or in those with CKD (6,(11)(12)(13).…”
mentioning
confidence: 99%
“…The most important finding in this paper was that the apo E genotype is a major determinant in urinary Gla excretion, which is consistent with observations that also serum vitamin K levels ) and the extent of osteocalcin carboxylation are strongly dependent on the apo E genotype (Beavan et al 2005;Pilkey et al 2007). …”
Section: Discussionsupporting
confidence: 75%
“…While 1 study reported decreasing ucOC concentrations in men and women with age [7] , 2 studies found no age effect in males or females [18,19] , and 2 other studies showed increasing concentrations with age in women [20,21] . The osteoblastic activity is age dependent, leading to changes in osteocalcin synthesis with age [22] .…”
Section: Introductionmentioning
confidence: 99%